Analysis of Antithrombotic Therapy after Cardioembolic Stroke Due to Atrial Fibrillation or Flutter. Issue 2 (February 2013) - Peterson, Evan J.; Reaves, Anne B.; Smith, Jennifer L.; Oliphant, Carrie S.
Background: Guidelines recommend that all patients with atrial fibrillation and a history of ischemic stroke should receive an anticoagulant. Prior analyses show that warfarin is underutilized in most populations. Objective: To examine the use of antithrombotic and anticoagulant therapy in patients with atrial fibrillation or flutter during the index hospitalization for acute, ischemic stroke. Methods: Retrospective electronic medical record review of 200 patients treated at a tertiary care hospital with a primary ICD-9 code for ischemic stroke and a secondary ICD-9 code for atrial fibrillation or flutter. Exclusion criteria were active bleeding, pregnancy, age less than 18, pre-existing warfarin allergy, or dabigatran use. Results: Fifty-two percent of patients received at least one dose of warfarin during the index hospitalization. There was no relationship between CHADS2 score and likelihood of receiving warfarin ( P > .05). There was no significant difference in adverse event rate in patients receiving warfarin compared to those receiving aspirin (3.8% vs 9.1%; P = .14), but the rate of hemorrhagic transformation was lower in patients receiving warfarin (1% vs 7%; P = .03). The composite of hemorrhagic stroke or hemorrhagic transformation was significantly lower in patients receiving bridging therapy (0% vs 11%; P = .03). Sixteen patients were readmitted for stroke within 3 months of discharge. Ten were readmitted for ischemic stroke, 3 for hemorrhagic stroke or hemorrhagic transformation, and 3 for systemic bleeding. Ten patients (62.5%) were receiving warfarin at readmission, but only one of these patients had a therapeutic INR. Conclusions: Warfarin was underutilized as secondary stroke prophylaxis in these high-risk patients. Bridging therapy appeared to be safe and was not associated with an increase in adverse events.